Implementasi Program Kampus Mengajar: Upaya Peningkatan Kualitas Lingkungan melalui Budidaya Maggot di SMKS 1 Pancasila Ambulu - Sila Rahmatina; Astri Widyaruli Anggraeni (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Organic waste is the residue of naturally degradable material, usually from humans, animals, and plants. Every day there are many kinds of organic waste that can be processed through a variety of processing. One way is to use it as a medium for breeding or breeding BSF flies. (Black Soldier Fly). The team from the university teaches this activity using organic garbage that is used as the primary material for growing BSF flies. The expected results of this training are aimed at optimizing the commercial value of BSF fly flies with the use of organic waste from the market or households. The working procedures for cultivating maggot are: 1) Preparing the tools and materials, 2) Making room for the maggot, 3) Putting the garbage in the container that has been made, 4) Covering the maggo container with cloth, 5) The maggot container is placed in a moist place. By reducing waste production, we not only preserve the environment, but also open up opportunities to improve the economic well-being of individuals, families and even the school environment.